2023
DOI: 10.3390/nano13081392
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Wettability Modification of Aluminum Surface through Single-Shot Nanosecond Laser Processing

Abstract: Conversion of a regular metal surface to a superhydrophobic one has great appeal because of the wide range of potential applications such as anti-fouling, anti-corrosion, and anti-icing. One promising technique is to modify surface wettability by laser processing to form nano-micro hierarchical structures with various patterns, such as pillars, grooves, and grids, followed by an aging process in the air or additional chemical processes. Surface processing is typically a lengthy process. Herein, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It is important to understand how to fabricate the desired topography and impose favorable chemistry on engineering metal substrates for desired wettability. It has been widely demonstrated that the wettability state of a solid surface can be changed by micro/nanostructuring of the surface. Fabrication techniques such as thermal oxidation, chemical vapor deposition, laser structuring, and plasma spray were widely used to create wetting properties based on two primary factors, and those are surface chemistry and surface micro-/nanostructures. Laser processing of metal surfaces is a reliable technique to produce superhydrophilic or superhydrophobic materials, depending on the surface energy of the material. Furthermore, a femtosecond laser with its good consistency, high precision, and negligible heat-affected zone is a one-step solution for creating multifunctional surfaces. Modification of the surface morphology under ultrafast laser irradiation is mainly carried out by ablation of a localized area with a focused beam, which makes it possible to change both the chemical composition of the material and the surface microstructure. …”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand how to fabricate the desired topography and impose favorable chemistry on engineering metal substrates for desired wettability. It has been widely demonstrated that the wettability state of a solid surface can be changed by micro/nanostructuring of the surface. Fabrication techniques such as thermal oxidation, chemical vapor deposition, laser structuring, and plasma spray were widely used to create wetting properties based on two primary factors, and those are surface chemistry and surface micro-/nanostructures. Laser processing of metal surfaces is a reliable technique to produce superhydrophilic or superhydrophobic materials, depending on the surface energy of the material. Furthermore, a femtosecond laser with its good consistency, high precision, and negligible heat-affected zone is a one-step solution for creating multifunctional surfaces. Modification of the surface morphology under ultrafast laser irradiation is mainly carried out by ablation of a localized area with a focused beam, which makes it possible to change both the chemical composition of the material and the surface microstructure. …”
Section: Introductionmentioning
confidence: 99%